Predictive Model and Precaution for Oral Mucositis During Chemo-Radiotherapy in Nasopharyngeal Carcinoma Patients - Li, Pei-Jing; Li, Kai-Xin; Jin, Ting; Lin, Hua-Ming; Fang, Jia-Ben; Yang, Shuang-Yan; Shen, Wei; Chen, Jia; Zhang, Jiang; Chen, Xiao-Zhong; Chen, Ming; Chen, Yuan-Yuan (Frontiers in Oncology, 2020)
Purpose To explore risk factors for severe acute oral mucositis of nasopharyngeal carcinoma (NPC) patients receiving chemo-radiotherapy, build predictive models and determine prevent measures. Methods and materials Two hundred and seventy NPC patients receiving radical chemo-radiotherapy were included. Oral mucosa structure was contoured by oral cavity contour (OCC) and mucosa surface contour (MSC) methods. Oral mucositis during treatment was prospectively evaluated and divided into severe mucositis group (grade ≥ 3) and non-severe mucositis group (grade ＜ 3) according to RTOG criteria. Nineteen clinical features and 19 dosimetric parameters were included in analysis, least absolute shrinkage and selection operator (LASSO) logistic regression model was used to construct a risk score (RS) system. Results Two predictive models were built based on the two delineation methods. MSC based model is more simplified one, it includes body mass index (BMI) classification before radiation, retropharyngeal lymph node (RLN) irradiation status and MSC V55%, RS = -1.890 +0.073 (BMI classification) + 0.217 (RLN irradiation) + 0.074 (MSC V55%). The cut-off of MSC based RS is -0.168, with an area under curve (AUC) of 0.752 (95%CI: 0.691-0.812), a specificity of 0.579 and a sensitivity of 0.838. OCC based model involved more variables, RS= -6.794+0.194 (BMI classification) + 0.303 (RT Technique) + 0.067 (Concurrent Nimotuzumab) + 0.329 (RLN irradiation) + 0.040 (OCC V15%) + 0.145 (OCC V60%). The cut-off of OCC based RS is -0.924, with an AUC of 0.763 (95%CI: 0.702-0.824), a specificity of 0.632 and a sensitivity of 0.787. The performance of these two models have no significant difference (P = 0.619). Conclusion We constructed two risk score predictive models for severe oral mucositis based on clinical features and dosimetric parameters of nasopharyngeal carcinoma patients receiving chemo-radiotherapy, which might help to discriminate high risk population that susceptible to severe oral mucositis and individualize treatment plan to prevent it.